Using drone-mounted cameras for on-site body documentation: 3D mapping and active survey - Urbanová, Petra; Jurda, Mikoláš; Vojtíšek, Tomáš; Krajsa, Jan (Forensic science international, 2017)
Recent advances in unmanned aerial technology have substantially lowered the cost associated with aerial imagery. As a result, forensic practitioners are today presented with easy low-cost access to aerial photographs at remote locations. The present paper aims to explore boundaries in which the low-end drone technology can operate as professional crime scene equipment, and to test the prospects of aerial 3D modeling in the forensic context. The study was based on recent forensic cases of falls from height admitted for postmortem examinations. Three mock outdoor forensic scenes featuring a dummy, skeletal remains and artificial blood were constructed at an abandoned quarry and subsequently documented using a commercial DJI Phantom 2 drone equipped with a GoPro HERO 4 digital camera. In two of the experiments, the purpose was to conduct aerial and ground-view photography and to process the acquired images with a photogrammetry protocol (using Agisoft PhotoScan® 1.2.6) in order to generate 3D textured models. The third experiment tested the employment of drone-based video recordings in mapping scattered body parts. The results show that drone-based aerial photography is capable of producing high-quality images, which are appropriate for building accurate large-scale 3D models of a forensic scene. If, however, high-resolution top-down three-dimensional scene documentation featuring details on a corpse or other physical evidence is required, we recommend building a multi-resolution model by processing aerial and ground-view imagery separately. The video survey showed that using an overview recording for seeking out scattered body parts was efficient. In contrast, the less easy-to-spot evidence, such as bloodstains, was detected only after having been marked properly with crime scene equipment.
Keywords: Imaging, Three-Dimensional; Photogrammetry; soudní vědy; audiovizuální záznam; Humans; Video Recording; Aerial photography; letadla; krevní skvrny; Blood Stains; Computer Simulation; technologie dálkového snímání; lidé; Forensic Sciences; fotogrammetrie; Drones; Real-time survey; Remote Sensing Technology; počítačová simulace; Photography; tělesné pozůstatky; Aircraft; Forensic scene documentation; fotografování; zobrazování trojrozměrné; Body Remains; 3D scene mapping